Peran Keluarga dengan Frekuensi Kekambuhan Klien Skizofrenia - Ruspawan Dewa Made; Sumirta I Nengah (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2013)
The purpose of this study to analyse the relationship between the family's role with the frequency of relaps client Schizophrenia. The role of the family is important in the carre of Schizophrenia clients in the provide and supervision of medication and control the expression emotion patient families. Design of this research is Analytical Descriptive Correlational study. By Cross Sectional approach. Data was collected by non probaility technic with consesutive sampling from 47 respondents. Data analysis techniques using the Product Moment Correlation Test with α=0,05. The results shown the average value of family roles of 55,57 and the average relaps clients Schizophrenia of 4.02 times. P-value of 0.0001, and values r=- 0.610 with p0.05 so that H0 is rejected, then it can be stated there is a strong relationship between the role of the Family with the frequency of relaps Client Schizophrenia at the Polyclinic Mental Hospital Province of Bali.